Aging Out of Foster Care: Homelessness, Post-Secondary Education, and Employment. Issue 1 (1st January 2018) - Rosenberg, Rachel; Kim, Youngmi
ABSTRACT: Research has shown that youth aging out of the foster care system experience an increased risk for several adverse adult outcomes (e.g., homelessness, unemployment, low educational attainment). Yet, fewer studies have examined the impact of homelessness on adult outcomes. The current study uses National Youth in Transition Database (NYTD) to examine the associations between homelessness and two outcomes, post-secondary education and employment status, for transition-aged foster youth ( N = 4, 235). This study found that youth who experienced homelessness between 19 and 21 years were less likely to have post-secondary education or full-time employment, controlling for individual and foster care characteristics.